Stress increases GABAergic neurotransmission in CRF neurons of the central amygdala and bed nucleus stria terminalis. (August 2016) - Partridge, John G.; Forcelli, Patrick A.; Luo, Ruixi; Cashdan, Jonah M.; Schulkin, Jay; Valentino, Rita J.; Vicini, Stefano
Abstract: Corticotrophin Releasing Factor (CRF) is a critical stress-related neuropeptide in major output pathways of the amygdala, including the central nucleus (CeA), and in a key projection target of the CeA, the bed nucleus of the stria terminalis (BnST). While progress has been made in understanding the contributions and characteristics of CRF as a neuropeptide in rodent behavior, little attention has been committed to determine the properties and synaptic physiology of specific populations of CRF-expressing (CRF + ) and non-expressing (CRF − ) neurons in the CeA and BnST. Here, we fill this gap by electrophysiologically characterizing distinct neuronal subtypes in CeA and BnST. Crossing tdTomato or channelrhodopsin-2 (ChR2-YFP) reporter mice to those expressing Cre-recombinase under the CRF promoter allowed us to identify and manipulate CRF + and CRF − neurons in CeA and BnST, the two largest areas with fluorescently labeled neurons in these mice. We optogenetically activated CRF + neurons to elicit action potentials or synaptic responses in CRF + and CRF − neurons. We found that GABA is the predominant co-transmitter in CRF + neurons within the CeA and BnST. CRF + neurons are highly interconnected with CRF − neurons and to a lesser extent with CRF + neurons. CRF + and CRF − neurons differentially express tonic GABA currents. Chronic, unpredictable stress increase the amplitude of evoked IPSCs and connectivity between CRF + neurons, but not between CRF + and CRF − neurons in both regions. We propose that reciprocal inhibition of interconnected neurons controls CRF + output in these nuclei. Highlights: CRF neurons in BnST and CeA and are functionally GABAergic. CRF + neurons synapse on both CRF − and CRF + neurons. Chronic stress upregulates synaptic connections between CRF + neurons.